Role of Ubiquitination in PTEN Cellular Homeostasis and Its Implications in GB Drug Resistance - Xia, Qin; Ali, Sakhawat; Liu, Liqun; Li, Yang; Liu, Xuefeng; Zhang, Lingqiang; Dong, Lei (Frontiers in Oncology, 2020)
Glioblastoma (GB) is the most common and aggressive brain malignancy, characterized by heterogeneity, rapid cell proliferation, and drug resistance. Loss of phosphatase and tensin homolog (PTEN) function frequently occurs in GB. However, therapeutic approaches targeting hyperactivated PI3K-AKT have not yielded promising outcomes because of the multiple functions of PTEN and intricacies in its regulation. Premature and absolute loss of PTEN activity tends to result in cellular senescence, which condition cannot be tolerated by cancer cells. Accordingly, monoallelic loss of PTEN is usually observed at tumor inception, and absolute loss of PTEN activity may occur at the late stage of gliomagenesis. PTEN, a crucial tumor suppressor, exhibits phosphatase-dependent/independent activities to maintain the homeostatic regulation of numerous physiological processes. Aberrant PTEN homeostasis mainly regulated at the post-translational level renders cells susceptible to tumorigenesis and drug resistance, particularly in GB. Ubiquitylation-mediated degradation or deregulated intracellular localization of PTEN hijacks cell growth rheostat control for neoplastic remodeling. Functional inactivation of PTEN mediated by the overexpression of ubiquitin ligases (E3s) renders GB cells adaptive to PTEN loss, which confers resistance to EGFR tyrosine kinase inhibitors and immunotherapies. In this review, we propose that glioma cells develop oncogenic addiction to the E3s-PTEN axis, promoting their growth and proliferation. Antitumor strategies involving PTEN-targeting E3 ligase inhibitors can restore the tumor-suppressive environment. E3 inhibitors can collectively reactivate PTEN and potentially be used as next-generation treatment against deadly malignancies such as GB.